1980
DOI: 10.1007/bf00580599
|View full text |Cite
|
Sign up to set email alerts
|

Unusual complication of soft tissue calcifications in chronic renal disease: The articular erosions

Abstract: A rare complication, articular bone erosions adjacent to peri-articular calcifications, was observed in patients undergoing chronic haemodialysis. Three cases are described and the discussion describes the pathogenesis of the lesion, which, as far as is known by the authors, has not yet been reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 5 publications
0
1
0
3
Order By: Relevance
“…Meltzer et al [10] reported a case of a 73-year-old black woman on chronic hemodialysis with tumoral calcinosis eroding the iliac crest. Meneghello et al [16] reported periarticular subchondral bone erosion adjacent to soft tissue calcification in a chronic renal dialysis patient. Steinbach et al [12] reported on tumoral calcinosis with bony erosion along the humeral head and femoral neck.…”
Section: Discussionmentioning
confidence: 99%
“…Meltzer et al [10] reported a case of a 73-year-old black woman on chronic hemodialysis with tumoral calcinosis eroding the iliac crest. Meneghello et al [16] reported periarticular subchondral bone erosion adjacent to soft tissue calcification in a chronic renal dialysis patient. Steinbach et al [12] reported on tumoral calcinosis with bony erosion along the humeral head and femoral neck.…”
Section: Discussionmentioning
confidence: 99%
“…Отличие эрозий при ПГПТ заключается в меньшей частоте кальцификации окружающих мягких тканей, сопутствующей эрозивному поражению. При нормализации уровня ПТГ отмечена положительная динамика эрозивного поражения суставов [77].…”
Section: эрозивная артропатия при первичном гиперпаратиреозеunclassified
“…Les deux premières avaient largement érodé la corticale et détruit un bonne partie de l'ilion et de l'ischion de patientes atteintes de néphrite chronique nécessitant des épurations extrarénales répétées [6].…”
Section: Calcinose Tumorale éRosiveunclassified
“…L'hyperpression de son contenu en revanche plaide en faveur d'un processus mécanique susceptible de comprimer et de détruire le tissu osseux. Elle corrobore les constatations et la théorie déjà avancée par Ménéghello [6].…”
Section: Calcinose Tumorale éRosiveunclassified